PARTICIPATION OF FARMER HOUSEHOLD NON-CONTRIBUTION ASSISTANCE RECIPIENT IN THE NATIONAL HEALTH INSURANCE PROGRAMME IN INDONESIA (Proceedings of the International Conference on Public Health, 2017)
Indonesia has set the achievement of Universal Health Coverage in 2019. Community participation in the national health insurance programme is the key to success, especially independent community groups (non-beneficiaries) in premium payments. Participation of farmer household non-contribution assistance recipient in the national health insurance programme is very low. Therefore, this study aims to analyze the factors that influence the participation of farmer households non- contribution assistance recipient in Jember District (agricultural center in East Java, Indonesia). This research used quantitative analytical method with observational approach. The independent variables of the study consist of the level of knowledge, the need on health insurance, the ability to pay the premium. Dependent variable was participation in health insurance programme. Data analysis using logistic regression. The results showed that the level of knowledge has a significant influence on the willingness of respondents to participate in the programme NHI with Odds ratio of 0.214. The need for health insurance also has a significant influence on the willingness of the respondents to participate in the NHI programme with the Odds ratio of 0.077.
Keywords: participation, farmer household, health insurance